Study of Flotation of Charcoal Fines Regarding Feed Size Distribution and Collector Concentration - Castro Rojas, Camila; Monique Brum Walter, Nicole; Gustavo Mendes de Jesus, Leandro (International Journal of Scientific Research in Science and Technology, 2024)
The cement industry Mato Grosso do Sul state in Brazil charge fines of coke and charcoal as their main fuels. Charcoal, upon arriving at the industry, is subjected to sizing steps (crushing, grinding and sieving), which is essential for a quick burning of the combustibles, generating heat to the cement production process. The coarse fraction of the charcoal sizing process is characterized by a high ash content and, consequently, a lower carbon content. To solve the problem, flotation presents itself as a process with potential for application. The aim of the work is to evaluate the feasibility of using different concentrations of collectors and particle size ranges to evaluate the feasibility of concentrating carbonaceous material through the flotation process. The tests were carried out on a bench flotation machine. The machine's agitator had a speed of 19.5 rpm and the flotation cell had a capacity of 0.75 l. The test products, concentrate and tailings, were subjected to ash and moisture tests. Through the results it was possible to notice that the lowest ash contents are in the coarser fractions, which is 1.0 mm, and the highest ash contents are in the feed less than 0.500 mm and less than 0.250 mm. The fraction with the greatest recovery potential is 0.250 mm with a percentage of 17.5% in mass of the recovered concentrate. In relation to the collector, the best carbonaceous recovery is found at a concentration of 10000 g/t, obtaining a maximum percentage of 79.1%.
Keywords: Charcoal tailings; Charcoal tailings flotation; Tailings concentration